Ina, kapatid, anak - Chionglo, Mel; Brocka, Lino; Chionglo, Mel; Baltazar, Conrado; Salvador, Augusto; Monteverde, Lily; Solis, Charito; Rodriguez, Lolita; Locsin, Rio (Regal Films, 1984)
Tells the story of half-sisters competing for the love of men. Emilia, played by Charito Solis, seeks the love that her father shows to the more favored daughter, Pura. Played by Lolita Rodriguez, Pura is after the attention of a man seduced by Emilia into marriage to spite her.